قواعد المنشأ في إطار منطقة التجارة الحرة العربية الكبرى - سيور, فراس (Latakia University Journal - Economic and Legal Sciences Series, 2015)
بينت تجربة التطبيق الفعلي لمنطقة التجارة الحرة العربية الكبرى خلال الفترة الممتدة بين عامي 1998 م- 2005 م، وجود العديد من المعوقات التي التعترض سير المبادلات التجارية العربية، وتحول دون الارتقلء بواقع العلاقات الاقتصادية بين الدول العربية، ولعل أبرز العقبات التي أفرغت اتفاقية المنطقة من مضمونها كانت قواعد المنشأ التفصيلية للسلع العربية. وعليه يهدفُ هذا المبحث إلى تسليط الضوء على قواعد المنشأ كأداة السياسة التجارية المستخدمة في اتفاقيات التجارة، كوسيلة لمواجهة ظاهرة التسلل العشوائي للسلع غير العربية إلى داخل الدول الأعضاء في اتفلقية المنطقة، حيث يوضَّحُ هذا البحثُ ماهية هذه القواعد وأهميتها بعد التطرق إلى أهمية منطقة التجارة الحرة العربية الكبرى بالنسبة للدول العربية. This research showed the experience of the actual application of the Free Trade Area of the Greater Arab during the period between 1998- 2005. There are many obstacles that hinder the progress of trade exchanges Arabic, and prevent the upgrading by the economic relations between the Arab states, and perhaps the most prominent obstacles that emptied agreement region of its content the detailed rules of origin for Arab goods. Accordingly, this research aims to shed light on the rules of origin as an instrument of trade policy instruments used in trade agreements, and as a means to cope with phenomenon of infiltration random goods of non-Arab to the inside of the Member states of the Convention on the region, as it demonstrates this research what these rules and their importance after addressing the importance of trade area Greater Arab Free for the Arab countries.